Negative plate and lithium ion secondary battery

By using high -content silicon carbon composite particles in lithium ion batteries and controlling its reaction in thermal testing, the SEI film problem caused by the expansion of the negative material of the silicon -based material, realizing high -ratio, energy density and excellent excellent Metrology and cycle life.

CN119381404APending Publication Date: 2025-01-28ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411543073.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The large volume expansion of the silicon-based anode material with high doping amount in existing lithium-ion batteries during the lithium-ion alloying/dealloyation process leads to the rupture and reformation of the solid electrolyte interface (SEI) film, causing the gradual attenuation of the specific capacity of the battery. and internal resistance increase, affecting rate performance and cycle life.

Method used

Adopt high-content silicon carbon composite particles as negative active substances, and through the thermostatic test of controlling negative active coatings under the nitrogen atmosphere, the increase in mass percentage in the range of 700 ° C-900 ° C is 0.3 % -3 % In order to adjust the amount of silicon carbon composite particles, improve the speed of lithium embedded and lithium -embedded balance, and form a stable SEI film.

Benefits of technology

It improves the capacity and energy density of the secondary battery of lithium ion, and has excellent percentage performance and cycle life, avoiding the breakdown of the SEI membrane and the decline in battery performance caused by re -formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381404A_ABST
    Figure CN119381404A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative electrode plate and a lithium ion secondary battery, the negative electrode plate comprises a negative electrode current collector and a negative electrode active coating located on at least one side surface of the negative electrode current collector; the negative electrode active coating comprises a negative electrode active material, and the negative electrode active material comprises silicon-carbon composite particles; the mass content of the silicon-carbon composite particles in the negative electrode active material is 60%-100%; and in a thermogravimetric test of the negative electrode active coating in a nitrogen atmosphere, the increment of the mass percent is 0.3%-3% in a range of 700 DEG C-900 DEG C. The negative plate provided by the invention adopts high-content silicon-carbon composite particles as a negative active material, so that the specific capacity and energy density of the negative electrode are greatly improved, and the lithium ion secondary battery composed of the negative plate has the advantages of high specific capacity and high energy density, and also has excellent rate capability and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a lithium ion secondary battery. Background Art

[0002] With the widespread application of portable electronic devices, electric vehicles, and energy storage components, the development of lithium-ion batteries (LIBs) with higher capacity is of great significance. Among the negative electrode materials for lithium-ion batteries, the theoretical gram capacity of graphite negative electrode is 372mAh / g, which is currently close to the limit. Silicon-based negative electrode materials are representative negative electrode materials for the next generation of lithium-ion batteries due to their high theoretical capacity (4200mAh / g), suitable operating voltage, and high natural abundance. Therefore, the prior art often adopts increasing the doping amount of silicon-based negative electrode materials in silicon negative electrodes to improve the specific capacity and energy density of lithium-ion batteries. However, the inherent large volume expansion (~400%) of highly doped silicon-based negative electrode materials during the lithium ion alloying / de-alloying process will lead to continuous rupture and reformation of the solid electrolyte interface (SEI) film. Each time a new SEI film is formed, part of the lithium ions will be consumed, resulting in a gradual attenuation of the battery specific capacity. At the same time, the thickness of the SEI film will increase during the continuous rupture and reformation process, resulting in an increase in the internal resistance of the battery, which seriously affects the rate performance and cycle life of the battery, greatly hindering the practical application of lithium-ion batteries with high doping amounts of silicon-based negative electrode materials, and greatly limiting the advantages of high specific capacity and high energy density of lithium-ion batteries with high doping amounts of silicon-based negative electrode materials. Summary of the invention

[0003] The purpose of the present invention is to overcome the above problems existing in the prior art, and provide a negative electrode sheet and a lithium ion secondary battery including the negative electrode sheet. The negative electrode sheet of the present invention uses a high content of silicon-carbon composite particles as the negative electrode active material, which greatly improves the specific capacity and energy density of the negative electrode, and the lithium ion secondary battery composed of the negative electrode sheet has the advantages of high specific capacity and high energy density, and has excellent rate performance and cycle life.

[0004] A first aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector; the negative electrode active coating comprises a negative electrode active material, the negative electrode active material comprises silicon-carbon composite particles; the mass content of the silicon-carbon composite particles in the negative electrode active material is 60%-100%;

[0005] In a thermogravimetric test of the negative electrode active coating in a nitrogen atmosphere, within the range of 700° C. to 900° C., the increase in mass percentage is 0.3% to 3%.

[0006] A second aspect of the present invention provides a lithium ion secondary battery, wherein the lithium ion secondary battery comprises the negative electrode sheet described in the first aspect of the present invention.

[0007] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0008] (1) The negative electrode sheet of the present invention uses high-content silicon-carbon composite particles as the negative electrode active material, which greatly improves the specific capacity and energy density of the negative electrode. The lithium-ion secondary battery composed of the negative electrode sheet can also have the advantages of high specific capacity and high energy density;

[0009] (2) The negative electrode sheet of the present invention can ensure that the lithium-ion secondary battery has excellent rate performance and cycle life while having high specific capacity and energy density by controlling the increase in mass percentage of the negative electrode active coating within the temperature range of 700°C-900°C in a thermogravimetric test under a nitrogen atmosphere to be 0.3%-3%.

[0010] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 Shown is a comparison diagram of thermogravimetric curves of the negative electrode active coating in a nitrogen atmosphere in an example of the present invention.

[0012] Figure 2 The figure shows a comparison of differential thermogravimetric curves of the negative electrode active coating in a nitrogen atmosphere in one example of the present invention.

[0013] Figure 3 The figure shows the Raman spectrum of the negative electrode conductive agent in one example of the present invention.

[0014] Figure 4 Shown is a Raman spectrum of silicon-carbon composite particles in an example of the present invention.

[0015] Figure 5 Shown is a cross-sectional SEM image of a negative electrode sheet in one embodiment of the present invention. DETAILED DESCRIPTION

[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0017] A first aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector; the negative electrode active coating comprises a negative electrode active material, the negative electrode active material comprises silicon-carbon composite particles; the mass content of the silicon-carbon composite particles in the negative electrode active material is 60%-100%, for example, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95% or 100%;

[0018] In a thermogravimetric test of the negative electrode active coating under a nitrogen atmosphere, the increase in mass percentage within the range of 700° C. to 900° C. is 0.3%-3%, for example, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3%.

[0019] First, the mass content of the silicon-carbon composite particles contained in the negative electrode active material of the negative electrode sheet of the present invention is 60%-100%. The present invention greatly improves the specific capacity and energy density of the negative electrode sheet by using a high content of silicon-carbon composite particles as the negative electrode active material, and when the mass content of the silicon-carbon composite particles in the negative electrode active material is 100%, the negative electrode sheet of the present invention can be a pure silicon-carbon negative electrode sheet with excellent specific capacity and energy density.

[0020] Furthermore, the negative electrode sheet of the present invention can adjust the amount of silicon-carbon composite particles with high reactivity and activity in the negative electrode active coating by controlling the increase in mass percentage of the negative electrode active coating in the temperature range of 700°C-900°C in a thermogravimetric test under a nitrogen atmosphere to 0.3%-3%, so that the content of silicon-carbon composite materials in the negative electrode active coating that are easy to alloy with lithium ions during the battery cycle is effectively controlled, which is beneficial to improving the lithium insertion speed and lithium insertion balance performance of the negative electrode active coating, so that the insertion and extraction process of lithium ions on the surface of the negative electrode active coating will be more uniform, which is helpful to form a more stable SEI film, so that the SEI film always maintains structural integrity during the cycle without obvious thickening and rupture, avoiding the thickening of the SEI film and the increase of its internal resistance due to excessive mass content of silicon-carbon composite particles, thereby ensuring that the lithium ion secondary battery can have excellent rate performance and cycle life while having high specific capacity and energy density.

[0021] When the mass percentage increase of the negative electrode active coating in the temperature range of 700℃-900℃ in the thermogravimetric test under a nitrogen atmosphere is less than 0.3%, it means that there are too few highly reactive silicon-carbon composite particles among all the silicon-carbon composite particles, which will lead to a decrease in the lithium ion insertion rate, a decrease in the uniformity and integrity of the SEI film, and easily cause a decrease in the battery specific capacity, rate performance and cycle performance; when the mass percentage increase of the negative electrode active coating in the temperature range of 700℃-900℃ in the thermogravimetric test under a nitrogen atmosphere is greater than 3%, it means that there are too many highly reactive silicon-carbon composite particles among all the silicon-carbon composite particles, which will affect the balance performance of the lithium ion insertion and extraction process, affect the stability of the SEI film, and be easily affected by electrolyte erosion and side reactions in the later stage of the battery cycle, causing continuous damage and reformation of the SEI film, increasing the internal resistance of the lithium ion secondary battery, and causing serious polarization, which is not conducive to the improvement of the rate performance of the lithium ion secondary battery. Therefore, it is necessary to adjust the amount of highly reactive and active silicon-carbon composite particles in the negative electrode active coating by controlling the increase in mass percentage of the negative electrode active coating in the temperature range of 700°C-900°C, so as to avoid the decrease in battery rate performance and cycle performance caused by poor stability and uniformity of the SEI film of the negative electrode active coating with high silicon content, thereby better exerting the advantages of high specific capacity and high energy density of lithium-ion batteries with high silicon-based negative electrode material doping amount.

[0022] like Figure 1 As shown, it is a thermogravimetric curve of the negative electrode active coating in an example of the present invention under a nitrogen atmosphere; in a nitrogen atmosphere, the temperature of the negative electrode active coating of the present invention is gradually increased to 900°C at a certain heating rate. In the temperature range of 700-900°C, the negative electrode active coating of the present invention has a slow weight increase phenomenon, and the increase in mass percentage is measured to be 0.3%-3%. It should be noted that the calculation method of the mass percentage increase in the temperature range of 700-900°C in the thermogravimetric test of the negative electrode active coating in a nitrogen atmosphere is to record the weight corresponding to the highest point of the increase in 700-900°C as M1, and the weight of the negative electrode active coating corresponding to the starting position where the mass percentage begins to increase is recorded as M0, and the mass percentage increase in the range of 700-900°C = (M1-M0) / M0×100%. The mass percentage of the negative electrode active coating increases within this temperature range because some silicon-carbon composite particles serving as negative electrode active materials can undergo a slow chemical reaction with nitrogen at high temperatures. At high temperatures, the dangling bonds of some silicon-carbon composite particles will react with inert nitrogen, which reflects their high reactivity and activity. These highly reactive silicon-carbon composite particles are easy to alloy with lithium during the battery cycle and have a fast lithium insertion speed, which is beneficial to improving rate performance and cycle performance.

[0023] In one example, the mass content of the silicon-carbon composite particles in the negative electrode active material is 90%-100%.

[0024] In one example, in a thermogravimetric test of the negative electrode active coating in a nitrogen atmosphere, within the range of 700° C. to 900° C., the increase in mass percentage is 0.6% to 1%.

[0025] In the present invention, the negative electrode active coating has a weight loss rate of 5%-6.5% at 900°C in a thermogravimetric test under a nitrogen atmosphere, for example, 5%, 5.1%, 5.2%, 5.3%, 5.4%, 5.5%, 5.6%, 5.7%, 5.8%, 5.9%, 6%, 6.1%, 6.2%, 6.3%, 6.4% or 6.5%. In a nitrogen atmosphere, the temperature of the negative electrode active coating of the present invention is increased to 900°C at a certain heating rate, and its overall weight loss rate is tested at 900°C to be 5%-6.5%. It should be noted that the weight loss rate of the negative electrode active coating at 900°C in a thermogravimetric test under a nitrogen atmosphere is calculated by recording its weight at the end of the test at 900°C as M2, and the weight of the original negative electrode active coating as M, and the weight loss rate at 900°C = M2 / M×100%. In this process, the main weight-loss material comes from the binder in the negative electrode active coating. By controlling the weight loss rate of the negative electrode active coating at 900°C in a thermogravimetric test under a nitrogen atmosphere to 5%-6.5%, the uneven stress distribution inside the electrode caused by insufficient binder can be avoided, so that the thickness of the formed SEI film is thin and has a certain integrity. In addition, the weight loss rate of the negative electrode active coating at a specific temperature can be reasonably controlled to reduce local stress concentration, which is helpful to form a more uniform SEI film, thereby improving the structural stability of the negative electrode active coating with a high silicon content, thereby improving the rate performance and cycle life of the high silicon content lithium ion battery. Moreover, under the premise of controlling the mass percentage increase of the negative electrode active coating at a specific temperature under a nitrogen atmosphere to 0.3%-3%, further controlling its weight loss rate at 900°C to 5%-6.5% can also help improve the structural stability of the negative electrode sheet and reduce the damage to the structure of the negative electrode active coating caused by volume expansion, thereby further facilitating the formation of an SEI film with excellent stability, thereby improving the cycle performance and rate performance of the lithium ion secondary battery while ensuring high energy density.

[0026] In the present invention, the heating rate of the negative electrode active coating in a thermogravimetric test under a nitrogen atmosphere is 5° C. / min.

[0027] In the present invention, the initial temperature of the negative electrode active coating in a thermogravimetric test under a nitrogen atmosphere is 25°C.

[0028] In the present invention, by setting the heating rate and initial temperature of the thermogravimetric test within a specific range, the mass percentage increase of the negative electrode active coating within the range of 700°C-900°C and the weight loss rate at 900°C can be better controlled, avoiding faster mass loss due to excessively fast heating rate or excessively high initial temperature, affecting the temperature range and mass percentage increase corresponding to the reaction of silicon-carbon composite particles with nitrogen, thereby improving the repeatability and comparability of the thermogravimetric test, so that the regulation of the increase / weight loss rate of the thermogravimetric test can better reflect the various aspects of the performance of the lithium-ion secondary battery.

[0029] In the present invention, if Figure 2 , which is a differential thermogravimetric curve of the negative electrode active coating in a nitrogen atmosphere in an example of the present invention. In the thermogravimetric test of the negative electrode active coating in a nitrogen atmosphere of the present invention, the differential thermogravimetric curve has a first peak, a second peak and a third peak. The differential thermogravimetric curve (DTG), also known as the thermogravimetric differential curve, is a curve obtained by performing first-order derivative processing on the thermogravimetric curve (TG). It can reflect the change of the mass change rate of the sample with temperature or time. Through the differential thermogravimetric curve, the temperature range of each weight loss peak can be controlled more accurately, so as to more accurately control the type and content of the substance lost by the binder in the negative electrode active material of the present invention under different weight loss peaks, so that the negative electrode active coating can be easily alloyed with lithium ions during the battery cycle. Highly active silicon-carbon composite particles can match more suitable binders, which is conducive to further improving the lithium insertion speed and lithium insertion balance performance of the negative electrode active coating, improving the stability of the negative electrode SEI film, and improving the cycle performance and expansion performance of the lithium ion battery; moreover, the appropriate binder selection is conducive to inhibiting the cyclic expansion of high-content silicon-based composite particles, and ensuring that the proportion of active substances will not be reduced too much due to the addition of binders, thereby simultaneously improving the cycle performance and energy density of lithium ion secondary batteries. In addition, by controlling the weight loss peak position of the differential thermogravimetric curve, the overall decomposition temperature of the negative electrode active material can be kept high, and the binder will not decompose due to heat generation in the later stage of the battery cycle, thereby improving the long cycle performance of the lithium-ion secondary battery.

[0030] In one example, the first peak is located at 100°C-250°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C. The weight loss is slow at 100°C-250°C, and the weight loss in this temperature range is mainly small molecular organic matter in the negative electrode active coating. In another example, the first peak is located at 100°C-130°C.

[0031] In one example, the second peak is located at 270°C-340°C, such as 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C or 340°C. There is a sharp weight loss at 270°C-340°C, and the weight loss in this temperature range is mainly due to the cracking of a part of the binder. In another example, the second peak is located at 300°C-340°C.

[0032] In one example, the third peak is located at 350°C-550°C, for example, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C or 550°C. There is a sharp weight loss at 350°C-550°C, and the weight loss in this temperature range is mainly due to the pyrolysis of the residual binder in the negative electrode active material layer. In another example, the third peak is located at 400°C-530°C.

[0033] In one example, the ratio of the peak area of ​​the second peak to the peak area of ​​the third peak is 1:(1-1.5), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5.

[0034] The present invention can better match a suitable binder for high-activity silicon-carbon composite particles by adjusting the peak range at different temperatures and the peak area relationship between the second peak and the third peak, thereby facilitating further improving the lithium insertion speed and lithium insertion balance performance of the negative electrode active coating, improving the stability of the silicon-carbon composite particles, thereby improving the stability of the negative electrode SEI film, and further improving the cycle performance and expansion performance of the lithium ion battery.

[0035] In the present invention, the negative electrode active coating further comprises a negative electrode binder, and the negative electrode binder comprises a sodium-containing binder. The sodium-containing binder can be connected to Si through chemical bonds or intermolecular interactions (such as covalent bonds or hydrogen bonds), maintaining a close connection between Si particles, so that the binder can form a strong chemical bond connection with the silicon-carbon composite particles, and can also enhance the connection strength between the silicon-carbon composite particles and the particles, alleviate the cycle expansion of the negative electrode active material, and improve the stability of the negative electrode SEI film, thereby further improving the cycle performance and rate performance of the lithium-ion secondary battery.

[0036] In the present invention, the mass content of the negative electrode binder in the negative electrode active coating is 3%-6%, for example, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%.

[0037] In one example, the mass content of the negative electrode binder in the negative electrode active coating is 4%-4.5%.

[0038] In the present invention, the mass content of the sodium-containing binder in the negative electrode active coating is 2%-4%, for example, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9% or 4%.

[0039] In one example, the mass content of the sodium-containing binder in the negative electrode active coating is 2.5%-3%.

[0040] In the present invention, the content of element Si in the negative electrode active coating is c1, the content of element Na in the negative electrode active coating is c2, c1 and c2 satisfy: 33≤c1 / c2≤63, for example, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 44.5, 44.6, 44.7, 44.8, 44.9, 45, 45.5, 46, 46.5, 47, 47.5, 48, 48.5, 49, 49.5, 50, 50.5, 51, 51.5, 52, 52.5, 53, 53.5, 54, 54.5, 55, 55.5, 56, 56.5, 57, 58, 59, 60, 61, 62 or 63.

[0041] In one example, 47≤c1 / c2≤57.

[0042] In the present invention, the sodium-containing binder includes at least one of sodium carboxymethyl cellulose (CMC-Na) and sodium polyacrylate (PAA-Na). In one example, the second peak and the third peak of the differential thermogravimetric curve can be achieved by adjusting the addition of sodium carboxymethyl cellulose (CMC-Na) and sodium polyacrylate (PAA-Na).

[0043] In the present invention, the negative electrode binder further comprises at least one of polyvinylidene fluoride, polyacrylic acid, carboxymethyl cellulose and styrene butadiene rubber (SBR). When the negative electrode binder further comprises at least one of polyvinylidene fluoride, polyacrylic acid, carboxymethyl cellulose and styrene butadiene rubber, the weight loss part also comprises the pyrolysis of the above other negative electrode binders, such as styrene butadiene rubber, in the third peak of the differential thermogravimetric curve, i.e., in the temperature range of 350-550°C.

[0044] In the present invention, the content c1 of element Si in the negative electrode active coating can be 28.5%-44.5%, for example, 28.5%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 38.2%, 38.4%, 38.6%, 38.8%, 39%, 39.1%, 39.3%, 39.5%, 39.7%, 39.9%, 40%, 40%. .2%, 40.4%, 40.6%, 40.8%, 41%, 41.1%, 41.3%, 41.5%, 41.7%, 41.9%, 42%, 42.2%, 42.4%, 42.6%, 42.8%, 43%, 43.1%, 43.3%, 43.5%, 43.7%, 43.9%, 44%, 44.1%, 44.2%, 44.3%, 44.4% or 44.5%. By further controlling the content c1 of the element Si in the negative electrode active coating, it can be ensured that the active material of the negative electrode sheet of the present invention has high reactivity and activity, and a high content of silicon content is ensured, thereby improving the negative electrode to maintain high energy density during the battery cycle while having excellent lithium insertion speed, improving the stability of the SEI film, and further improving the energy density, rate performance and cycle performance of the lithium ion battery.

[0045] In one example, the content c1 of element Si in the negative electrode active coating is 42.7%-44.5%.

[0046] In the present invention, the content c2 of the element Na in the negative electrode active coating can be 0.5%-1.2%, for example, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, 1.1 or 1.2. By further controlling the content c2 of the element Na in the negative electrode active coating, it can be ensured that the negative electrode binder of the negative electrode sheet of the present invention has excellent chemical structure and properties, can better adapt to the volume change of high-content silicon-carbon composite particles, maintain the integrity and stability of the negative electrode structure, and improve the cycle stability of the high-silicon content negative electrode, thereby further improving the cycle performance of the lithium-ion secondary battery and improving expansion.

[0047] In one example, the content c2 of element Na in the negative electrode active coating is 0.9%-1%.

[0048] In the present invention, the negative electrode active coating further comprises a negative electrode conductive agent, and the Raman spectrum of the negative electrode conductive agent is as follows: Figure 3 The Raman spectrum of the negative electrode conductive agent in one example is shown; the Raman spectrum of the negative electrode conductive agent is at 1385 cm -1 -1389cm -1 There is a D peak, for example, at 1385 cm -1 、1386cm-1 、1387cm -1 、1388cm -1 or 1389cm -1 ; at 1590cm -1 -1595cm -1 There is a G peak, for example, at 1590 cm -1 、1591cm -1 、1592cm -1 、1593cm -1 、1594cm -1 or 1595cm -1 ; at 2670cm -1 -2675cm -1 There is a 2D peak, for example at 2670 cm -1 、2671cm -1 、2672cm -1 、2673cm -1 、2674cm -1 or 2675cm -1 .

[0049] In one example, the intensity ratio of the D peak to the G peak is 1:(35-40), for example, 1:35, 1:36, 1:37, 1:38, 1:39, 1:40.

[0050] In one example, the intensity ratio of the 2D peak to the G peak is 1:(5-7), for example 1:5, 1:5.1, 1:5.2, 1:5.3, 1:5.4, 1:5.5, 1:5.6, 1:5.7, 1:5.8, 1:5.9, 1:6, 1:6.1, 1:6.2, 1:6.3, 1:6.4, 1:6.5, 1:6.6, 1:6.7, 1:6.8, 1:6.9, 1:7.

[0051] When the positions of the D peak, G peak and 2D peak of the Raman spectrum of the negative electrode conductive agent are controlled within the above range, the negative electrode conductive agent not only has high-strength structural properties, but also has excellent flexibility, and can form a stable conductive network in the silicon-carbon composite particles, which helps the negative electrode active material with a high silicon-carbon composite particle content to maintain the integrity and stability of the high silicon content negative electrode sheet structure during repeated volume expansion and contraction, thereby improving the conductivity of the silicon-carbon composite particles and the stability of the SEI film of the silicon-carbon composite particles, thereby improving the cycle stability and cycle life of the negative electrode sheet.

[0052] When the intensity ratio of the D peak to the G peak and the intensity ratio of the 2D peak to the G peak are further controlled within the above range, the flexibility of the conductive network structure can be further improved, the structural stress between the high-content silicon-carbon composite particles can be buffered, the SEI film formed by the high-activity silicon-carbon composite particles can be stabilized, and the SEI film thickening caused by the continuous rupture of the SEI film of the high-silicon content negative electrode sheet can be avoided, the internal resistance of the battery is reduced, and it is helpful to further improve the rate performance and cycle life of the lithium-ion secondary battery.

[0053] In one example, the negative electrode conductive agent includes single-walled carbon nanotubes. Single-walled carbon nanotubes have extremely high electrical conductivity and can provide fast electron conduction channels for silicon-carbon composite particles, thereby helping to improve the conductivity of the battery, reduce the internal resistance of the battery, and further improve the energy density of the lithium-ion secondary battery.

[0054] In another example, the mass content of the negative electrode conductive agent in the negative electrode active coating is 0.5%-4%, for example, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3%, 3.5% or 4%. Because the conductivity of the silicon-carbon composite particles is low, when the content of the silicon-carbon composite particles is high, the conductivity of the negative electrode active coating will also become lower, so the content of the conductive agent should not be too little, otherwise it will cause the internal resistance of the battery to increase. Therefore, it is necessary to adjust the mass content of the negative electrode conductive agent in the negative electrode active coating to be greater than 0.5%. However, the content of the conductive agent should not be too much, because it will cause the gram capacity of the battery to decrease, affect the overall performance of the battery, and reduce the cycle life and stability. Therefore, it is necessary to adjust the mass content of the negative electrode conductive agent in the negative electrode active coating to be less than 4%.

[0055] In another example, the mass content of the negative electrode conductive agent in the negative electrode active coating is 0.5%-1.5%.

[0056] In the present invention, the mass content of the negative electrode active material in the negative electrode active coating is 90%-96%, for example, 90%, 91%, 92%, 93%, 94%, 95% or 96%. In one example, the mass content of the negative electrode active material in the negative electrode active coating is 91%-95%.

[0057] In the present invention, the silicon-carbon composite particles include a porous carbon skeleton and nano-silicon particles located in the porous carbon skeleton. The silicon-carbon composite particles of the present invention can obtain high reactivity and high activity by depositing nano-silicon particles in the porous carbon skeleton, and are easy to form alloys with lithium during the battery cycle, which is beneficial to improving the lithium insertion speed and lithium insertion balance performance of the negative electrode active coating, so that the embedding and extraction process of lithium ions on the surface of the negative electrode active coating will be more uniform, which is helpful to form a more stable SEI film, so that the SEI film always maintains structural integrity during the cycle process without obvious thickening and rupture, thereby further improving the energy density, rate performance and cycle performance of the lithium ion battery.

[0058] In one embodiment, the nano-silicon particles account for 30%-47.5% of the total mass of the silicon-carbon composite particles, for example, 30%, 31%, 32%, 32.5%, 33%, 34%, 35%, 36%, 37.5%, 38%, 39%, 40%, 41%, 42.5%, 43%, 44%, 45%, 46%, 47% or 47.5%.

[0059] In yet another example, the nano-silicon particles account for 45.5%-47.5% of the total mass of the silicon-carbon composite particles.

[0060] In the present invention, a method for preparing silicon-carbon composite particles is also provided, and the specific preparation steps are as follows:

[0061] S1: providing a porous carbon skeleton, and heat-treating the porous carbon skeleton at 700°C-900°C (for example, 700°C, 750°C, 800°C, 850°C or 900°C) under inert gas protection for 6h-12h.

[0062] S2: Perform chemical vapor deposition on the porous carbon skeleton treated in S1, introduce silane gas under negative pressure, and react at 400℃-550℃ (for example, 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, 510℃, 520℃, 530℃, 540℃ or 550℃) for 3-6h, and repeat S2 operation 3-5 times.

[0063] S3: heat-treating the obtained porous carbon skeleton containing nano-silicon particles at 550°C-650°C (for example, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C or 650°C) under inert gas protection for 1h-3h.

[0064] S4: preparing a protective layer on the surface of the porous carbon skeleton composited with the obtained nano-silicon particles to obtain the silicon-carbon composite particles.

[0065] In step S4, a polymer binder needs to be added, and the polymer binder will form a protective layer on the surface of the porous carbon skeleton composited with nano-silicon particles, thereby providing a continuous conductive network for the silicon-carbon composite particles, improving their conductivity, and reducing the internal resistance of the battery.

[0066] In one example, the polymer binder includes at least one of polyaniline (PANi), polypyrrole (PPy), and polythiophene (PTh).

[0067] In the present invention, the negative electrode active material further includes a carbon-based material, and the carbon-based material includes at least one of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon and hard carbon. When the mass content of the silicon-carbon composite particles in the negative electrode active material is less than 100%, the negative electrode active material may include the above-mentioned carbon-based material.

[0068] In the present invention, the particle size Dv10 of the silicon-carbon composite particles may be 2 μm-5 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.

[0069] In one example, the particle size Dv10 of the silicon-carbon composite particles is 3 μm-4 μm.

[0070] In the present invention, the particle size Dv50 of the silicon-carbon composite particles is 6 μm-12 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm.

[0071] In one example, the particle size Dv50 of the silicon-carbon composite particles is 6 μm-10 μm.

[0072] In the present invention, the particle size Dv90 of the silicon-carbon composite particles is 12 μm-25 μm, for example, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm or 25 μm.

[0073] In one example, the particle size Dv90 of the silicon-carbon composite particles is 15 μm-23 μm.

[0074] Silicon-carbon materials such as silicon-carbon composite particles themselves have a high theoretical specific capacity. By controlling their particle size, their high specific capacity characteristics can be fully utilized, thereby further improving the unit mass energy density of high-silicon content negative electrode sheets, and then improving the overall energy density of lithium-ion secondary batteries; and silicon-carbon composite particles of appropriate size have a smaller volume expansion during the charge and discharge process, which is conducive to the formation of a more stable SEI film, and are suitable for negative electrode sheets with a higher silicon content, thereby extending the cycle life of lithium-ion secondary batteries and improving the rate performance of lithium-ion secondary batteries.

[0075] In the present invention, the Raman spectrum of the silicon-carbon composite particles is as follows: Figure 4 The Raman spectrum of silicon-carbon composite particles in one example is shown in FIG. -1 -480cm -1 (For example, 470cm -1 、471cm -1 、472cm -1 、473cm -1 、474cm -1 、475cm -1 、476cm -1 、477cm -1 、478cm -1 、479cm -1 or 480cm -1 ) has a characteristic peak 1 at 507cm -1 -517cm -1 (For example, 507cm -1 、508cm -1 、509cm -1 、510cm -1 、511cm -1 、512cm -1 、513cm -1 、514cm -1 、515cm -1 、516cm -1 or 517cm -1 ) has characteristic peak 2 at 1330cm -1 -1350cm -1 (For example, 1330cm -1 、1335cm -1 、1340cm -1 、1345cm -1 or 1350cm -1 ) has characteristic peak 3 at 1590cm -1 -1610cm -1 (For example, 1590cm -1 、1595cm -1 、1600cm -1 or 1605cm -1 )There is characteristic peak 4.

[0076] In the present invention, for the Raman spectrum of the silicon-carbon composite particles, the intensity I1 of the characteristic peak 1 and the intensity I2 of the characteristic peak 2 satisfy: I2 < I1; the intensity I3 of the characteristic peak 3 and the intensity I4 of the characteristic peak 4 satisfy: 0.5 ≤ I3 / I4 ≤ 2, such as 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.

[0077] In one example, 0.7 ≤ I3 / I4 ≤ 1.

[0078] In the present invention, for the XRD diffraction pattern of the silicon-carbon composite particles, there is a diffraction peak 1 at 27.4° - 29.4° (such as 27.4°, 27.5°, 27.6°, 27.7°, 27.8°, 27.9°, 28°, 28.1°, 28.2°, 28.3°, 28.4°, 28.5°, 28.6°, 28.7°, 28.8°, 28.9°, 29°, 29.1°, 29.2°, 29.3° or 29.4°), and there is a diffraction peak 2 at 42.4° - 44.4° (such as 42.4°, 42.5°, 42.6°, 42.7°, 42.8°, 42.9°, 43°, 43.1°, 43.2°, 43.3°, 43.4°, 43.5°, 43.6°, 43.7°, 43.8°, 43.9°, 44°, 44.1°, 44.2°, 44.3° or 44.4°). The full width at half maximum W1 of the diffraction peak 1 and the full width at half maximum W2 of the diffraction peak 2 satisfy: 3° ≤ W1 + W2 ≤ 35°, such as 3°, 4°, 5°, 6°, 7°, 8°, 9°, 10°, 11°, 12°, 13°, 14°, 15°, 16°, 17°, 18°, 19°, 20°, 21°, 22°, 23°, 24°, 25°, 26°, 27°, 28°, 29°, 30°, 31°, 32°, 33°, 34° or 35°.

[0079] In one example, 11° ≤ W1 + W2 ≤ 13°.

[0080] The present invention can help improve the structural stability of the silicon-carbon composite particles by testing the Raman spectrum and XRD diffraction pattern of the silicon-carbon composite particles, and controlling the characteristic peaks or diffraction peaks within a suitable range and the intensity or position relationship between different characteristic peaks or diffraction peaks. The improved structural stability is conducive to the formation of a more stable and thinner SEI film, so that the silicon-carbon composite particles of the present invention are more suitable for use in negative electrode sheets with a high silicon content, thereby improving the volume expansion problem in the later stage of the cycle; in addition, the electrochemical properties of the silicon-carbon composite particles can be improved, the electronic structure and charge distribution can be optimized, the conductivity of the silicon-carbon composite particles themselves can be improved, and the decrease in the conductivity of the negative electrode active material due to excessive silicon-carbon composite particles can be avoided, thereby further improving the charge and discharge efficiency, rate performance and energy density of the lithium-ion secondary battery.

[0081] In the present invention, the surface density of the negative electrode active coating can be 1.9 mg / cm 2 -2.2mg / cm 2 , for example, 1.9 mg / cm 2 、1.91mg / cm 2 、1.92mg / cm 2 、1.93mg / cm 2 、1.94mg / cm 2 、1.95mg / cm 2 、1.96mg / cm 2 、1.97mg / cm 2 、1.98mg / cm 2 、1.99mg / cm 2 , 2mg / cm 2 , 2.01mg / cm 2 , 2.03mg / cm 2 , 2.05mg / cm 2 , 2.07mg / cm 2 , 2.09mg / cm 2 , 2.1mg / cm 2 , 2.12mg / cm 2 , 2.14mg / cm 2 , 2.16mg / cm 2 , 2.18mg / cm 2 or 2.2 mg / cm 2 .

[0082] In one example, the surface density of the negative electrode active coating is 2.05 mg / cm 2 -2.11mg / cm 2 .

[0083] In the present invention, the compaction density of the negative electrode active coating can be 0.7 g / cm 3 -0.9g / cm 3 , for example 0.7 g / cm 3 , 0.71g / cm 3 , 0.72g / cm 3 , 0.73g / cm 3 , 0.74g / cm 3 , 0.75g / cm 3 , 0.76g / cm 3 , 0.77g / cm 3 、0.78g / cm 3 , 0.79g / cm 3 , 0.8g / cm 3 、0.81g / cm 3 , 0.82g / cm 3 , 0.83g / cm 3 , 0.84g / cm 3 , 0.85g / cm 3 , 0.86g / cm 3 , 0.87g / cm 3 , 0.88g / cm 3 , 0.89g / cm 3 or 0.9g / cm 3 .

[0084] In one example, the compaction density of the negative electrode active coating is 0.8 mg / cm 2 -0.85mg / cm 2 .

[0085] In the present invention, the porosity of the negative electrode sheet may be 26%-29%, for example, 26%, 27%, 28% or 29%.

[0086] By further optimizing the areal density and tap density of the negative electrode active coating, the present invention can increase the content of active material per unit area, thereby improving the energy density of the battery. Moreover, an appropriate tap density can reduce the shedding and pulverization of the negative electrode active material, improving the cycle life of the battery. Additionally, by reasonably adjusting the areal density and tap density of the negative electrode active coating, it helps to control the increase in mass percentage of the negative electrode active coating during thermogravimetric testing, avoiding the mass increase of the negative electrode active coating occurring in an inappropriate temperature range, and thus enabling better regulation of the increase range of the negative electrode active coating, which is more conducive to the improvement of the performance of lithium-ion secondary batteries. Secondly, a reasonable porosity design can improve the wettability of the electrolyte, reduce the migration impedance of lithium ions in the negative electrode, enhance the conductivity of the negative electrode sheet with a high silicon content, and avoid the decrease in the conductivity of the negative electrode active material caused by the relatively large content of silicon-carbon composite particles, thereby further improving the charge-discharge rate and rate performance of the battery.

[0087] In the second aspect of the present invention, a lithium-ion secondary battery is provided, and the lithium-ion secondary battery includes the negative electrode sheet described in the first aspect of the present invention.

[0088] In the present invention, the lithium-ion secondary battery further includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a substance with the chemical formula Li a Ni x Co y Mn z M k O2, where 0.9 ≤ a ≤ 1.1 (such as 0.9, 1, or 1.1), 0.6 ≤ x ≤ 0.95 (such as 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, or 0.95), 0 < y ≤ 0.2 (such as 0.05, 0.1, 0.15, or 0.2), 0 < z ≤ 0.2 (such as 0.05, 0.1, 0.15, or 0.2), 0 ≤ k ≤ 0.05 (such as 0, 0.01, 0.02, 0.03, 0.04, or 0.05), and M is selected from at least one of Al, Zr, B, Y, Sr, W, Ti, and Nb.

[0089] In one example, 0.8 ≤ x ≤ 0.9.

[0090] In the present invention, a ternary material with a high nickel content can be used as the positive electrode active material. The high nickel ternary material has a higher specific capacity, average operating voltage and energy density due to its high nickel content. This high energy density enables the battery to store more electrical energy under the same volume or weight. When it is used in conjunction with a negative electrode sheet with a high silicon content, the specific capacity and energy density of the battery can be further improved. At the same time, the special changes and designs of the nano-, composite and alloying of silicon-carbon composite particles in the present invention can avoid the problems of structural instability and surface side reactions of the high nickel ternary material when used in conjunction with a negative electrode sheet with a high silicon content. The two materials play a synergistic role, so that the lithium-ion secondary battery obtains a more stable active material structure, while improving the specific capacity and energy density of the battery, it is also expected to achieve more stable cycle performance and longer cycle life.

[0091] In the present invention, the lithium-ion secondary battery further comprises a separator, and the separator can be prepared by conventional methods in the art or obtained commercially.

[0092] In the present invention, the lithium-ion secondary battery also includes an electrolyte, which is composed of an organic solvent, an additive and an electrolyte lithium salt. The electrolyte lithium salt includes one or more of lithium hexafluorophosphate, bis(fluorosulfonyl)imide lithium salt, lithium tetrafluoroborate and lithium difluorooxalatoborate. The organic solvent includes one or more of carbonates, ethers and amides. The additive includes a lithium halide salt.

[0093] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0094] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.

[0095] The following examples serve to illustrate the present invention.

[0096] Example 1

[0097] Prepare as follows:

[0098] Preparation of silicon-carbon composite particles

[0099] S1: providing a porous carbon skeleton, and subjecting the porous carbon skeleton to a heat treatment at 800° C. under an inert gas protection for 6 hours.

[0100] S2: chemical vapor deposition was performed on the porous carbon skeleton treated in S1. Silane gas was introduced under negative pressure and reacted at 500° C. for 3 h. The S2 operation was repeated 3 times.

[0101] S3: heat-treating the obtained porous carbon skeleton containing nano-silicon particles at 600° C. under the protection of an inert gas for 1 hour to obtain the silicon-carbon composite particles.

[0102] S4: preparing a protective layer on the surface of the porous carbon skeleton composited with the obtained nano-silicon particles to obtain the silicon-carbon composite particles;

[0103] Among them, the nano-silicon particles account for 46.5% of the total mass of the silicon-carbon composite particles. The particle size Dv10 of the silicon-carbon composite particles is 3.5 μm, the particle size Dv50 is 8 μm, and the particle size Dv90 is 17 μm. The Raman spectrum of the silicon-carbon composite particles is as follows: Figure 4 As shown, the position of characteristic peak 1 is 472 cm -1 , the position of characteristic peak 2 is 507cm -1 The position of characteristic peak 3 is 1341 cm -1 , the position of characteristic peak 4 is 1594cm -1 , I2 <I1,I3 / I4=0.92;

[0104] In addition, the XRD diffraction spectrum of the silicon-carbon composite particles in this embodiment has a diffraction peak 1 at 28.5° and a diffraction peak 2 at 43.5°, and the half-peak width W1 of the diffraction peak 1 and the half-peak width W2 of the diffraction peak 2 add up to 12°.

[0105] Preparation of negative electrode

[0106] S5: The silicon-carbon composite particles obtained in S4, a binder, a conductive agent (according to a mass ratio of 92:4:4), and a solvent are prepared into a negative electrode slurry whose viscosity, solid content and uniformity meet the standards; wherein the binder includes sodium carboxymethyl cellulose, sodium polyacrylate and styrene-butadiene rubber, and the specific mass contents are respectively 2% sodium carboxymethyl cellulose, 1.5% sodium polyacrylate, and 0.5% styrene-butadiene rubber, wherein the sodium-containing binder is 3.5% in total and the negative electrode binder is 4% in total; the conductive agent is single-walled carbon nanotubes, and its Raman spectrum is as shown in FIG. Figure 3 shown.

[0107] S6: coating the negative electrode slurry on a 0.0035 mm copper foil to obtain a negative electrode active material layer with a thickness of 0.048 mm, and drying for 6 hours.

[0108] S7: rolling and cutting to obtain the negative electrode sheet;

[0109] Among them, the surface density of the negative electrode active coating is 2.09 mg / cm 2 The compaction density of the negative electrode active coating is 0.83g / cm 3 , the porosity of the negative electrode sheet is 27%.

[0110] Figure 5 , which is a cross-sectional SEM image of a negative electrode sheet provided in one example of the present invention.

[0111] Example 2 Group

[0112] The negative electrode sheet of Example 2 was prepared by referring to the method of Example 1, except that the mass content of the silicon-carbon composite particles in the negative electrode active material was changed, as shown below:

[0113] In Example 2-1, the negative electrode active material is changed to include both silicon-carbon composite particles and artificial graphite, and the mass ratio of the silicon-carbon composite particles to the artificial graphite is 60:40;

[0114] In Example 2-2, the negative electrode active material is changed to include both silicon-carbon composite particles and artificial graphite, and the mass ratio of the silicon-carbon composite particles to the artificial graphite is 80:20;

[0115] In Example 2-3, the negative electrode active material is changed to include both silicon-carbon composite particles and artificial graphite, and the mass ratio of the silicon-carbon composite particles to the artificial graphite is 90:10.

[0116] Example 3 Group

[0117] The negative electrode sheet of Example 3 was prepared by referring to the method of Example 1, except that the mass content of the sodium-containing binder in the negative electrode active coating was changed, as shown below:

[0118] Example 3-1, the mass ratio of sodium carboxymethyl cellulose to sodium polyacrylate remains unchanged, and the total amount of the two becomes 2%;

[0119] Example 3-2, the mass ratio of sodium carboxymethyl cellulose to sodium polyacrylate remains unchanged, and the total amount of the two becomes 4%;

[0120] In Example 3-3, the mass ratio of sodium carboxymethyl cellulose to sodium polyacrylate remains unchanged, and the total amount of the two becomes 3%.

[0121] Example 4 Group

[0122] The negative electrode sheet of the fourth embodiment is prepared by referring to the method of the first embodiment, except that the mass content of the negative electrode conductive agent in the negative electrode active coating is changed, as shown below:

[0123] In Example 4-1, the mass ratio of silicon-carbon composite particles, binder and conductive agent is 95.5:4:0.5;

[0124] In Example 4-2, the mass ratio of the silicon-carbon composite particles, the binder and the conductive agent is 94.5:4:1.5.

[0125] Example 5 Group

[0126] The negative electrode sheet of the Example 5 group was prepared by referring to the method of the Example 1, except that the mass content of the negative electrode binder in the negative electrode active coating was changed, and the sodium-containing binder was increased or decreased in equal proportion, as shown below:

[0127] In Example 5-1, the mass ratio of silicon-carbon composite particles, binder and conductive agent is 91.5:4.5:4;

[0128] In Example 5-2, the mass ratio of silicon-carbon composite particles, binder and conductive agent is 93:3:4;

[0129] In Example 5-3, the mass ratio of the silicon-carbon composite particles, the binder and the conductive agent is 90:6:4.

[0130] Example 6 Group

[0131] The negative electrode sheet of the sixth embodiment was prepared by referring to the method of the first embodiment, except that the specific operating conditions (such as rolling strength, etc.) during the preparation of the negative electrode sheet were changed, so that the surface density, compaction density or porosity of the negative electrode active coating was changed, as shown below:

[0132] Example 6-1, the surface density of the negative electrode active coating is 2.03 mg / cm 2 The compaction density of the negative electrode active coating is 0.8g / cm 3 , the porosity of the negative electrode sheet is 28%;

[0133] Example 6-2, the surface density of the negative electrode active coating is 2.17 mg / cm 2 The compaction density of the negative electrode active coating is 0.85g / cm 3 , the porosity of the negative electrode sheet is 26%.

[0134] Comparative Example 1

[0135] The negative electrode sheet of Comparative Example 1 was prepared by referring to the method of Example 1, with the only difference being that the mass content of the silicon-carbon composite particles in the negative electrode active material was changed, and the negative electrode active material was changed to contain both silicon-carbon composite particles and artificial graphite, and the mass ratio of silicon-carbon composite particles to artificial graphite was 40:60.

[0136] Comparative Example 2

[0137] The negative electrode sheet of Comparative Example 2 was prepared by referring to the method of Example 1, with the only difference being that the mass content of the silicon-carbon composite particles in the negative electrode active material was changed, and the negative electrode active material was changed to contain both silicon-carbon composite particles and artificial graphite, and the mass ratio of silicon-carbon composite particles to artificial graphite was 20:80.

[0138] Comparative Example 3

[0139] The negative electrode sheet of Comparative Example 3 was prepared by referring to the method of Example 1, with the only difference being that the mass content of the silicon-carbon composite particles in the negative electrode active material was changed, and the negative electrode active material was changed to pure artificial graphite, i.e., without silicon-carbon composite particles.

[0140] Comparative Example 4

[0141] The negative electrode sheet of Comparative Example 4 was prepared by referring to the method of Example 1, with the only difference being that ordinary silicon-carbon particles having the same particle size were used to replace the silicon-carbon composite particles prepared in Example 1, and the mass content of the ordinary silicon-carbon particles in the negative electrode active material was also 100%.

[0142] The specific parameters of the negative electrode active material layer in the above negative electrode sheet are shown in Table 1.

[0143] Table 1

[0144]

[0145] Negative electrode test example

[0146] The thermogravimetric curve and differential thermogravimetric curve of the negative electrode active coating of the negative electrode sheet of each of the above embodiments and comparative examples are tested, and the test steps are as follows:

[0147] S8: Separate the current collector and the negative electrode active coating of the negative electrode sheet, and collect the negative electrode active coating.

[0148] S9: Place the negative electrode active coating material into a thermogravimetric analyzer, heat the material through a programmed temperature control system under a nitrogen atmosphere, measure the mass change of the material through a detection system, and record the relationship between the mass change and temperature or time through a recording system.

[0149] S10: Collect thermogravimetric data of the negative electrode active coating, obtain a thermogravimetric curve, calculate the first-order derivative of the thermogravimetric data, plot the temperature, and obtain a differential thermogravimetric curve.

[0150] Figure 1 , which is a thermogravimetric curve of the negative electrode active coating provided in Example 1 of the present invention under a nitrogen atmosphere; Figure 2 The figure shows the differential thermogravimetric curve of the negative electrode active coating provided in Example 1 of the present invention under a nitrogen atmosphere. Figure 1 It can be seen from the figure that the negative electrode active coating of the present invention has a slow weight increase phenomenon within the range of 700°C-900°C. Figure 2 It can be seen that in the thermogravimetric test of the negative electrode active coating of the present invention under a nitrogen atmosphere, the differential thermogravimetric curve has a first peak, a second peak and a third peak, the first peak is located at 100℃-250℃, the second peak is located at 270℃-340℃, and the third peak is located at 350℃-550℃.

[0151] Then the increase (%) of the negative electrode active coating at 700°C-900°C, the weight loss rate (%) at 900°C and the peak values ​​of the differential thermogravimetric curve (the second peak and the third peak) are recorded. The peak temperature of the first peak is mainly related to the small molecular organic matter present in the negative electrode active coating, and the temperature change is not large, so it is not recorded in Table 2. See Table 2 for other test results.

[0152] Table 2

[0153]

[0154] In Table 2, the increase in the negative electrode active coating of Comparative Example 1 at 700°C-900°C is small, indicating that the silicon-carbon composite particles are difficult to react with nitrogen at this time and do not have high reactivity and high activity; the increase in the negative electrode active coating of Comparative Examples 2 and 3 at 700°C-900°C is negative, indicating that the negative electrode active coating at this time has material loss, mainly because the content of artificial graphite in the negative electrode active material is relatively high, especially in Comparative Examples 2 and 3. Therefore, when the negative electrode active coating is heated to 700°C-900°C in a nitrogen atmosphere, it will show a weightless state. Therefore, the increase is represented by a "-" sign to represent the weight loss in mass percentage.

[0155] Preparation of lithium-ion batteries

[0156] Preparation of positive electrode:

[0157] Lithium nickel cobalt manganese oxide (NCM955, Li 1.02 Ni 0.9 Co 0.05 Mn 0.05 Al 0.04 O2), polyvinylidene fluoride (PVDF), acetylene black and single-walled carbon nanotubes (CNT) are mixed in a mass ratio of 97:1.5:1.25:0.25, and a solvent N-methylpyrrolidone is added to obtain a positive electrode slurry through a vacuum mixer. The positive electrode slurry is evenly coated on a high-strength aluminum foil with a thickness of 10 μm. The aluminum foil coated with the positive electrode slurry is dried in a vacuum drying oven at 95°C for 12 hours, and the positive electrode sheet is rolled by a single-roll roller press, and then die-cut to obtain a positive electrode sheet.

[0158] Preparation of electrolyte:

[0159] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), EC / PC / PP / PA were mixed evenly in a mass ratio of 10 / 15 / 55 / 20, and then lithium hexafluorophosphate (LiPF6) with a total mass content of 14.38wt% based on the total mass content of the electrolyte was quickly added thereto as a lithium salt. After dissolution, 16wt% of fluoroethylene carbonate (FEC) based on the total mass content of the electrolyte, 2wt% of 1,3-propane sultone (PS), 2wt% of 1,3,6-hexanetrinitrile (HTCN), 2wt% of adiponitrile (ADN), and 1wt% of succinonitrile (SN) were added. The mixture was stirred evenly, and the desired electrolyte was obtained after passing the moisture and free acid tests.

[0160] Lamination process:

[0161] The die-cut positive electrode sheets and the corresponding negative electrode sheets of the embodiments and comparative examples were placed in a vacuum drying oven and baked at 90°C for 12 hours, and a diaphragm with a thickness of 8 μm containing a ceramic coating layer was selected as the diaphragm of the battery cell. The positive electrode sheets, diaphragms and negative electrode sheets were stacked in sequence by a stacking machine so that the diaphragm could separate the positive electrode sheets from the negative electrode sheets. Finally, a stacked core was obtained, in which the number of positive electrode sheets and negative electrode sheets were 22 and 23, respectively.

[0162] Packaging process:

[0163] The core stack is fixed into the welding mold, the positive and negative pole ears are welded respectively, and then fixed with high-temperature tape, and finally encapsulated with an aluminum-plastic film with a thickness of 0.113 mm.

[0164] Post-process:

[0165] The packaged dry cells were placed in an oven and baked at 90° C. for 48 hours. After the moisture test was qualified, the above electrolyte was injected, and after aging, formation, secondary sealing and sorting, the lithium ion secondary batteries of the embodiments and comparative examples were obtained.

[0166] Lithium-ion battery test example

[0167] The lithium ion secondary batteries obtained in the above examples and comparative examples were tested as follows, and the test results are recorded in Table 3:

[0168] 1. Mass energy density test:

[0169] En (discharge energy) = R1 (discharge capacity of the first cycle) * V1 (average discharge voltage of the first cycle), mass energy density ED = En / M (Wh / Kg), the test results are recorded in Table 3.

[0170] 2. 25℃ cycle performance test and lithium-ion battery specific capacity test:

[0171] The battery cell to be tested is transferred to a constant temperature room at 25±1°C and allowed to stand for 30 minutes. It is charged to 4.3V at a constant current of 1.8C (5760mAh), and charged to a charging current of less than 0.05C (160mAh) at a constant voltage of 4.3V, and allowed to stand for 10 minutes. The thickness of the battery cell tested by a thickness gauge is Qx (X=number of cycles, specifically 600T), and is discharged to 2.5V at a constant current of 4C (12800mAh), and allowed to stand for 10 minutes. The above test is a complete cycle process, and its discharge capacity (mAh) is recorded as Rx (X=number of cycles), the capacity retention rate of the lithium ion battery Ux=Rx / R1*100%, the specific capacity of the lithium ion battery=discharge capacity Rx divided by the mass of the positive electrode active material, in units of mAh / g, and the test results are recorded in Table 3.

[0172] 3. Rate performance test:

[0173] Transfer the lithium-ion battery cell to be tested to a constant temperature room at 25±1℃ and let it stand for 30 minutes, charge it to 4.3V at a constant current of 0.5C, charge it to a charging current of less than 0.05C (160mAh) at a constant voltage of 4.3V, let it stand for 10 minutes, and discharge it to 2.5V at constant currents of 0.5C, 1C, 2C, and 5C, respectively, and calculate the capacity retention rate at different discharge rates. The calculation formula is: discharge capacity at each current / charge capacity at 0.5C, and the test results are recorded in Table 3.

[0174] Table 3

[0175]

[0176]

[0177] From the analysis of Table 3, it can be seen that the negative electrode sheet of the present invention adopts a high content of silicon-carbon composite particles as the negative electrode active material, which is different from Comparative Examples 1 to 3, greatly improving the specific capacity and energy density of the lithium-ion secondary battery composed of the negative electrode sheet, and can also have excellent rate performance and cycle life.

[0178] From Comparative Examples 1 to 3, the mass content of artificial graphite in the negative electrode active material continues to increase, and the cycle stability of the lithium-ion secondary battery becomes better. Therefore, the 25°C capacity retention rate of Comparative Examples 1 to 3 is slightly better than that of Example 1. However, the specific capacity and energy density of the lithium-ion secondary batteries of Comparative Examples 1 to 3 will be severely attenuated, which greatly limits the advantages of high specific capacity and energy density of silicon-containing lithium-ion secondary batteries.

[0179] Comparative Example 4 Compared with Example 1, the increase in the mass percentage of the negative electrode active coating in the temperature range of 700°C-900°C is relatively large, indicating that the amount of highly reactive and highly active silicon-carbon particles in the negative electrode active coating is relatively large. In this case, although the high silicon-doped lithium-ion battery can obtain a relatively high specific capacity and energy density, it will seriously affect the long cycle performance, cycle stability and rate performance of the lithium-ion battery, thereby causing the battery capacity retention rate and rate performance to decrease, greatly hindering the practical application of lithium-ion batteries with high silicon content, and greatly limiting the advantages of high specific capacity and energy density of lithium-ion batteries with high silicon content. In Example 1 of the present invention, by controlling the mass percentage increase of the negative electrode active coating in the range of 700°C-900°C to be within a suitable range, it can ensure that the lithium-ion secondary battery has excellent rate performance and cycle life while having high specific capacity and energy density.

[0180] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector; the negative electrode active coating comprises a negative electrode active material, and the negative electrode active material comprises silicon-carbon composite particles; the mass content of the silicon-carbon composite particles in the negative electrode active material is 60%-100%; In a thermogravimetric test of the negative electrode active coating in a nitrogen atmosphere, within the range of 700° C. to 900° C., the increase in mass percentage is 0.3% to 3%.

2. The negative electrode sheet according to claim 1, wherein: In a thermogravimetric test of the negative electrode active coating in a nitrogen atmosphere, the mass percentage increase is 0.6%-1% in the range of 700°C-900°C; And / or, in a thermogravimetric test of the negative electrode active coating in a nitrogen atmosphere, the weight loss rate at 900° C. is 5%-6.5%.

3. The negative electrode sheet according to claim 1 or 2, wherein: In a thermogravimetric test of the negative electrode active coating in a nitrogen atmosphere, a differential thermogravimetric curve has a first peak, a second peak and a third peak; Preferably, the first peak is located at 100°C-250°C, the second peak is located at 270°C-340°C, and the third peak is located at 350°C-550°C; Preferably, the ratio of the peak area of ​​the second peak to the peak area of ​​the third peak is 1:(1-1.5).

4. The negative electrode sheet according to claim 1 or 2, wherein: The negative electrode active coating further comprises a negative electrode binder, wherein the negative electrode binder comprises a sodium-containing binder; Preferably, the content of element Si in the negative electrode active coating is c1, the content of element Na in the negative electrode active coating is c2, and c1 and c2 satisfy: 33≤c1 / c2≤63; more preferably 47≤c1 / c2≤57.

5. The negative electrode sheet according to claim 4, wherein: The sodium-containing binder includes at least one of sodium carboxymethyl cellulose and sodium polyacrylate; And / or, the negative electrode binder further comprises at least one of polyvinylidene fluoride, polyacrylic acid, carboxymethyl cellulose and styrene-butadiene rubber; And / or, the content c1 of element Si in the negative electrode active coating is 28.5%-44.5%; And / or, the content c2 of element Na in the negative electrode active coating is 0.5%-1.2%; preferably 0.9%-1%.

6. The negative electrode sheet according to claim 1 or 2, wherein: The negative electrode active coating also includes a negative electrode conductive agent, and the Raman spectrum of the negative electrode conductive agent is 1385cm -1 -1389cm -1 There is a D peak at 1590 cm -1 -1595cm -1 There is a G peak at 2670cm -1 -2675cm -1 There are 2D peaks; Preferably, the intensity ratio of the D peak to the G peak is 1:(35-40); Preferably, the intensity ratio of the 2D peak to the G peak is 1:(5-7); Preferably, the negative electrode conductive agent comprises single-walled carbon nanotubes; More preferably, the mass content of the negative electrode conductive agent in the negative electrode active coating is 0.5%-4%.

7. The negative electrode sheet according to claim 1 or 2, wherein: The silicon-carbon composite particles include a porous carbon skeleton and nano-silicon particles located in the porous carbon skeleton; preferably, the nano-silicon particles account for 30%-47.5% of the total mass of the silicon-carbon composite particles; And / or, the negative electrode active material further includes a carbon-based material, and the carbon-based material includes at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon and hard carbon.

8. The negative electrode sheet according to claim 1 or 2, wherein: The particle size Dv10 of the silicon-carbon composite particles is 2 μm-5 μm, the particle size Dv50 is 6 μm-12 μm, and the particle size Dv90 is 12 μm-25 μm; and / or, the Raman spectrum of the silicon-carbon composite particles has a characteristic peak 1 at 470 cm -1 -480 cm -1 a characteristic peak 2 at 507 cm -1 -517 cm -1 a characteristic peak 3 at 1330 cm -1 -1350 cm -1 a characteristic peak 4 at 1590 cm -1 -1610 cm -1 a characteristic peak 4; the intensity I1 of the characteristic peak 1 and the intensity I2 of the characteristic peak 2 satisfy: I2 < I1; the intensity I3 of the characteristic peak 3 and the intensity I4 of the characteristic peak 4 satisfy: 0.5 ≤ I3 / I4 ≤ 2; And / or, the XRD diffraction spectrum of the silicon-carbon composite particles has a diffraction peak 1 at 27.4°-29.4°, and a diffraction peak 2 at 42.4°-44.4°, and the half-peak width W1 of the diffraction peak 1 and the half-peak width W2 of the diffraction peak 2 satisfy: 3°≤W1+W2≤35°.

9. The negative electrode sheet according to claim 1 or 2, wherein: The surface density of the negative electrode active coating is 1.9 mg / cm 2 -2.2mg / cm 2 ; And / or, the compaction density of the negative electrode active coating is 0.7 g / cm 3 -0.9g / cm 3 .

10. A lithium ion secondary battery, characterized in that: The lithium ion secondary battery comprises the negative electrode sheet according to any one of claims 1 to 9.

11. The lithium ion secondary battery according to claim 10, wherein: The lithium ion secondary battery further includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a substance with the chemical formula Li a Ni x Co y Mn z M k O2, where 0.9 ≤ a ≤ 1.1, 0.6 ≤ x ≤ 0.95, 0 < y ≤ 0.2, 0 < z ≤ 0.2, 0 ≤ k ≤ 0.05, and M is selected from at least one of Al, Zr, B, Y, Sr, W, Ti, and Nb; preferably, 0.8 ≤ x ≤ 0.9.

Citation Information

Cited By

  • Lithium-ion battery

    EP4819291A1